Pengaruh Perkembangan Teknologi Informasi dan Layanan Telekomunikasi Terhadap Peningkatan Pendapatan Masyarakat Indonesia - Wardhana, Ariyani (Bina Nusantara University, 2011)
Information technology development grows faster every year. This phenomena makes opportunity for new businesses and business expansions in various industrial segments, especially for small and medium industries. Information technology is a part of support value in Porter’s value chain to optimalize industry performance. Application development, capacity amount, and various facilities in mobile phone access such as voice call, SMS, MMS, GPRS, 3G, 4G, and Vas add value to support primary business activities in each sector to earn more income. Income raise in many industries will bring impacts in national income and prosperity.